Morphological and cytological effects of two herbicides on Tetraploid wheat (Triticum durum L.) - Razu, MH; Zaman, S; Akhter, R; Rahman, MM; Rahaman, M Hamidur; Mazid, MA; Kabir, G (Journal of Bio-Science, 2014)
Context: In order to control weeds many chemicals are being used which may change the morphological and cytological constitution of plant. Objectives: To study the morphological and cytological effects of herbicides on tetraploid wheat. Materials and Methods: Two herbicides namely, Topstar and Fielder with three different concentrations of each were used along with control in the present study. Seeds of tetraploid wheat were treated for 6 hours with each concentration and some of the treated seeds were allowed to germinate in the petri dishes, while some were sown in the earthen pot. Morphological study was done for both laboratory and pot grown plants. In case of cytological study, mitotic data was recorded using the root tip cells and meiotic data was collected from inflorescence at pre-mature stage of pot grown plant. Results: In this experiment, data on morphological study such as germination percentage, days required in germination, coleoptile length, root length, plant height, ear length, tiller-number/pot, seed/ear, grain-weight/ear and 100 grain-weight indicated that treatment with Fielder decreased these characters with the increase of doses. In case of plant height, Topstar showed increased result than Fielder and control. Moreover, characters like ear length and seed/ear showed little variation among the doses of Topstar compared to control. Similarly, data on cytological study such as interphase chromosome volume (ICV), mitotic index (MI), % of pollen sterility, mitotic and meiotic abnormalities were found to be increased with increasing concentration of both herbicides. Main chromosomal irregularities were chromosome fragments, bridges, laggards, single and multiple chromatid bridges with laggard or fragment, stickiness etc. Conclusion: From the study of morphological and cytological effects of two herbicides along with control it can be concluded that these chemicals had adverse impacts which reduced the yield of wheat. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17736 J. bio-sci. 20: 143-151, 2012